Diversity of transgene integration and gene-editing events in wheat (Triticum aestivum L.) transgenic plants generated using Agrobacterium-mediated transformation - Lopos, Louie Cris; Bykova, Natalia V.; Robinson, Janeen; Brown, Susan; Ward, Kerry; Bilichak, Andriy (Frontiers in Genome Editing, 2023)
Improvement in agronomic traits in crops through gene editing (GE) relies on efficient transformation protocols for delivering the CRISPR/Cas9-coded transgenes. Recently, a few embryogenesis-related genes have been described, the co-delivery of which significantly increases the transformation efficiency with reduced genotype-dependency. Here, we characterized the transgenic and GE events in wheat (cv. Fielder) when transformed with GROWTH-REGULATING FACTOR 4 (GRF4) and its cofactor GRF-INTERACTING FACTOR 1 (GIF1) chimeric gene. Transformation efficiency in our experiments ranged from 22% to 68%, and the editing events were faithfully propagated into the following generation. Both low- and high-copy-number integration events were recovered in the T0 population with various levels of integrity of the left and right T-DNA borders. We also generated a population of wheat plants with 10 different gRNAs targeting 30 loci in the genome. A comparison of the epigenetic profiles at the target sites and editing efficiency revealed a significant positive correlation between chromatin accessibility and mutagenesis rate. Overall, the preliminary screening of transgene quality and GE events in the T0 population of plants regenerated through the co-delivery of GRF–GIF can allow for the propagation of the best candidates for further phenotypic analysis.